Pronunciation simplification strategies in child language. Experimental study - Krivickaitė, Eglė (Taikomoji kalbotyra, 2017)
The aim of this study is to determine the strategies of pronunciation simplification. The sample of the study consisted of 288 Lithuanian children: 96 preschool age children (4;00–4;11), 95 pre-primary school age children (6;00–6;11) and 97 junior primary school age children (8;00–8;11). The data were collected using a non-word repetition task in Lithuanian.The results of the research have shown that Lithuanian children apply universal strategies of pronunciation simplification, mostly substitution and omission; other strategies such as consonant assimilation, metathesis, sound migration to another syllable and sound addition were much less frequent. Also the results show that children possibly apply associations with real Lithuanian words or their derivational forms.The research has demonstrated that the ability to repeat different structure words is related to the rules of Lithuanian phonotactics. Consonant clusters which are typical of Lithuanian words were pronounced accurately, whereas clusters which are rare in Lithuanian words were simplified in their pronunciation. Age was an important factor in the present study: older children repeated non-words more accurately. Older children have a larger lexicon and eventually develop it further; they learn new consonant clusters, which they are capable to pronounce more accurately.
Keywords: language acquisition; non-word repetition test; phonotactics; pronunciation simplification strategies; consonant clusters